An investigation into the volume change characteristics of loess like soil in Mount Moorosi Village in Lesotho - Damane, Monica (Department of Civil Engineering, 2020)
The Mount Moorosi village is situated in the Senqu River Valley of southern Lesotho, within the Stormberg landform. The integrity and aesthetic appearance of nearly all the structures in this area are undermined by recurrent cracks. At present, no apparent institutionalised effort had been conducted to investigate the source of this problem. The crack patterns were associated with the possible volume change of the underlaying loess like soil. This soil has caused a disastrous failure to brittle civil engineering structures in various parts of the world. Its behaviour is attributed to sand and silt particles bonded by minerals, which become active upon saturation and induce hydrocollapse settlement. This study characterised the volume change properties of the underlaid deposits in Mount Moorosi. The research utilised representative samples from trial pits in the study region to perform laboratory experiments such as the Atterberg limits, wet sieving, sedimentation, free swell, x-ray diffraction, scanning electron microscope and slaking. The consolidated undrained tests and hydrocollapse potential were also determined from the GEOCOMP triaxial and Global Digital System oedometer, respectively. Results revealed that Mount Moorosi is generally underlaid by a more than 3 m thickness of low plasticity (9 to 17 %) silty-sandy loess. The material had significant warping (up to 27 mm) in linear shrinkage that illustrated potential inducement of detrimental stresses to the superimposed structures during drying. The identification and quantification of the mineralogy composition clearly evidenced the passive minerals (quartz, feldspar and mica) to be predominant (86 %), while the active phases (kaolinite, carbonates, sulfates, halides, the oxides and hydroxides of aluminum and iron) were subordinate (14 %), which substantiated potential soil settlement upon wetting. Furthermore, the micrographs depicted structures that synergistically enhanced the collapse properties of the tested deposits. These included the porous clays, silts bonded by clay and silts coated with clay, which all rendered a metastable fabric. A comparison of the stressstrain graphical plots from the consolidated undrained tests at the field and saturated moisture contents indicated a drastic reduction (up to 73 %) in deviator stress at saturated water content. This was attributed to the augmentation of the interparticle spaces, caused by a rise of up to 337 kPa in pore water pressure. Shear strength parameters obtained from Mohr’s failure envelopes were also decreased by up to 80 %. The hydrocollapse index measured from the oedometer tests ranged from 10 to 15 % at a vertical stress of 200 kPa. It indicated severe settlement problems for structures constructed on this soil. This was caused by the loss in shear strength of the soil under the saturated conditions and a high slaking mechanism that reached a maximum rating of 4. Generally, the mineralogy composition, morphology, saturated shear strength, slaking and hydrocollapse index collectively indicated the possibility of soil volume decrease. In fact, the check for serviceability limit state demonstrated a settlement that exceeded the tolerable value of 50 mm. The cracks observed on structures were, therefore, related to soil settlement. This study recommends further research on suitable ground techniques to minimise settlement, thereby improving the durability of structures. Moreover, investigations should be conducted to understand the pressure induced by warping during shrinkage.